The Relationship between Cohesiveness and Effectiveness in Small Isolated Groups: A Field Study - Vallacher, Robin R.; Seymour, George E.; Gunderson, E. K. (1974)
The relationship between cohesiveness and group effectiveness among groups of men at U.S. Antarctic research stations was investigated. Cohesiveness indices based upon positive intermember attraction were negatively correlated with incidence of emotional symptomatology within station groups, but were, for the most part, unrelated to supervisors' and group members' perceptions of performance. Indices based upon negative intermember attraction (conflict), in contrast, were significantly related to perceptions of performance, particularly those of supervisors, but were unrelated to symptomatology. The differential importance of positive and negative intermember attraction for different aspects of group functioning was discussed, and the probable moderating role of task versus social-relations orientations in the cohesiveness-effectiveness relationship was suggested.